Forkhead box O3 longevity genotype may attenuate the impact of hypertension on risk of intracerebral haemorrhage. Issue 11 (3rd November 2022) - Nakagawa, Kazuma; Chen, Randi; Greenberg, Steven M.; Ross, G. Webster; Willcox, Bradley J.; Donlon, Timothy A.; Allsopp, Richard C.; Willcox, D. Craig; Morris, Brian J.; Masaki, Kamal H.
Abstract : Objective: Since the G allele of forkhead box O3 ( FOXO3 ) single nucleotide polymorphism (SNP) rs2802292 is associated with resilience and longevity, ostensibly by mitigating the adverse effects of chronic cardiometabolic stress on mortality, our aim was to determine the association between the FOXO3 SNP rs2802292 genotype and risk of hypertension-mediated intracerebral haemorrhage (ICH). Methods: From a prospective population-based cohort of Japanese American men from the Kuakini Honolulu Heart Program (KHHP), age-adjusted prevalence of ICH by hypertension was assessed for the whole cohort after stratifying by FOXO3 genotype. Cox regression models, adjusted for age, cardiovascular risk factors and, FOXO3 and APOE genotypes, were utilized to determine relative risk of hypertension's effect on ICH. All models were created for the whole cohort and stratified by FOXO3 G -allele carriage vs. TT genotype. Results: Among 6469 men free of baseline stroke, FOXO3 G -allele carriage was seen in 3009 (46.5%) participants. Overall, 183 participants developed ICH over the 34-year follow-up period. Age-adjusted ICH incidence was 0.90 vs. 1.32 per 1000 person-years follow-up in those without and with hypertension, respectively ( P  = 0.002). After stratifying by FOXO3 genotype, this association was no longer significant in G allele carriers. In the whole cohort, hypertension was an independent predictor of ICH (relative risk [RR] = 1.70, 95% confidence interval [CI] 1.25, 2.32; P  = 0.0007). In stratified analyses, hypertension remained an independent predictor of ICH among the FOXO3 TT -genotype group (RR = 2.02, 95% CI 1.33, 3.07; P  = 0.001), but not in FOXO3 G -allele carriers (RR = 1.39, 95% CI 0.88, 2.19; P  = 0.15). Conclusions: The longevity-associated FOXO3   G allele may attenuate the impact of hypertension on ICH risk.